2011
DOI: 10.2478/v10059-011-0006-x
|View full text |Cite
|
Sign up to set email alerts
|

How Do People Resolve Conflict Between Implicit and Explicit Attitudes?

Abstract: How Do People Resolve Conflict Between Implicit and Explicit Attitudes? How do implicit attitudes influence behavior when they are in conflict with explicit attitudes? In Study 1, smokers' negative implicit attitudes and positive explicit attitudes towards smoking were activated. Then emotions were measured. The stronger the negative implicit attitudes that the smokers held, the stronger the conflict experienced. Study 2 showed that cognitive capacity allows for this conflict, as positive explicit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…An additional finding of the present study was that IED was related to behavior at all three measurement points, which was also the case in former studies [29,30,[32][33][34]69]. In the current study, the relationship was negative.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…An additional finding of the present study was that IED was related to behavior at all three measurement points, which was also the case in former studies [29,30,[32][33][34]69]. In the current study, the relationship was negative.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, the non-acceptance of dissonance had a positive and thereby desirable effect on the intention to reduce RMC. Future studies should investigate in which contexts dissonance results in healthy behaviors, as it was the case in the present study, and in which contexts dissonance results in rather unhealthy behaviors, as demonstrated in former studies [32][33][34]. Shedding light on these questions would allow interventions to consciously induce dissonance in order to achieve certain behavior changes.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations